2023
DOI: 10.1161/strokeaha.122.041394
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Recommendations for Standardized Data Elements, Scales, and Time Segmentations in Studies of Human Circadian/Diurnal Biology and Stroke

Abstract: Increasing evidence indicates that circadian and diurnal rhythms robustly influence stroke onset, mechanism, progression, recovery, and response to therapy in human patients. Pioneering initial investigations yielded important insights but were often single-center series, used basic imaging approaches, and used conflicting definitions of key data elements, including what constitutes daytime versus nighttime. Contemporary methodologic advances in human neurovascular investigation have the potential to substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Time of transfer was operationally defined as the time of MRI in the primary stroke center and was dichotomized into day (7:00–22:59) versus night (23:00–6:59), with time-epochs decided a priori based on the CIRCA network consortium recommendations. 4 Infarct volumes on diffusion-weighted imaging (DWI) were manually outlined based on DWI signal intensity and encompassed the entire area of bright DWI signal intensity. Areas of decreased apparent diffusion coefficient with subtle DWI signal changes were also segmented.…”
Section: Methodsmentioning
confidence: 99%
“…Time of transfer was operationally defined as the time of MRI in the primary stroke center and was dichotomized into day (7:00–22:59) versus night (23:00–6:59), with time-epochs decided a priori based on the CIRCA network consortium recommendations. 4 Infarct volumes on diffusion-weighted imaging (DWI) were manually outlined based on DWI signal intensity and encompassed the entire area of bright DWI signal intensity. Areas of decreased apparent diffusion coefficient with subtle DWI signal changes were also segmented.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical data regarding time-of-day-dependent patterns in stroke incidence are variable (Table ), but broadly suggest a peak incidence in the morning, 188,189 with a second lower peak in the evening (Box 1). 188,[190][191][192] A meta-analysis of 31 studies involving 11 816 patients found that the first detection of stroke (ischemic and hemorrhagic) and transient ischemic attack occurred between 06:00 and 12:00 in 37% of patients, between 12:00 and 18:00 in 26% of patients, between 18:00 and 00:00 in 19% of patients, and between 00:00 and 06:00 in 18% of patients 26 (note: as per recent recommendations, 193 all times in the following are shown in a 24-hour clock format). The morning surge has been found to be independent of variables including age, sex and known cardiovascular risk factors such as hypertension and diabetes.…”
Section: Clinical Evidence and Implications Of A Time-of-day-dependen...mentioning
confidence: 99%
“…187,189,243,244 More studies suggested a better outcome for patients treated with EVT in the morning, 187,189,243 but one study found better outcome in patients admitted between 18:00 to 08:00. 244 A recent retrospective multicenter study of 9357 patients with stroke treated with EVT, with patients grouped into four 6-hour time-blocks (as per recent consensus recommendations 193 ) found an association between time of treatment with clinical outcomes at 90 days after stroke. 187 Patients treated in the morning between 05:00 and 10:59 had better clinical outcomes compared with treatment at other times of the day.…”
Section: Chrono-pharmacology In Stroke and Clinical Trial Implicationsmentioning
confidence: 99%
“…4 Although it cannot be directly measured in the context of stroke of unknown onset (latent variable), there is a pathophysiological rationale that this time metric would differ markedly in the 2 clinical scenarios observed in patients with stroke of unknown onset: wake-up stroke (WUS) and daytime unwitnessed stroke (non-WUS). Indeed, endogenously generated circadian rhythms but also diurnal rhythms (sleep or wakefulness, light, temperature, etc) 5 will induce variations in blood pressure, heart rate variability, and hemostatic processes that will especially increase the risk of the stroke in the early morning hours. This suggests that in most patients with WUS, the time elapsed since stroke onset is short (eg, <4.5 hours), a hypothesis supported by comparative quantitative analyses of FLAIR signal intensity in patients with known symptom onset and WUS.…”
mentioning
confidence: 99%
“…Being able to include data from the EXTEND trial would have been particularly valuable because it relied primarily on computed tomography imaging and could have provided additional geographic diversity of participants, 2 which may be important from an ethnic perspective, but also because geographic location is an important modulator of diurnal rhythms. 5 Another important point to consider is that at the time the WAKE-UP and THAWS trials were conducted, the overwhelming benefit of endovascular therapy for stroke of unknown onset had not yet been demonstrated. Therefore, although 18% of the patients included in this article had a large vessel occlusion—conservatively defined as an internal carotid artery or M1 occlusion—, they did not receive mechanical thrombectomy, which is now considered standard of care without the need for advanced imaging.…”
mentioning
confidence: 99%